Digital memory in Brazil : a fragmented and elastic negationist remembrance of the dictatorship - Balbino, Leda (Digital activism and society., 2023)
The memory of the military dictatorship (1964-1985) in Brazil is still under dispute after almost 40 years of re-democratization. Narratives contradicting the memory critical to this regime started to spread digitally in the 2000s, with former army captain Jair Bolsonaro becoming one of its leading exponents. Digital Memory in Brazil draws on the results of three case studies to determine the strategies and practices applied by the Brazilian far-right government of Bolsonaro (2019-2023) to construct a negationist digital memory of the Brazilian dictatorship. Social media were crucial for Bolsonaro's 2018 electoral campaign and government. Leda Balbino focuses on investigating this memory through its discursive processes and the impact of the digital medium on its development. Identifying a fragmented and elastic memory with the political purpose of promoting an authoritarian agenda under the vision of a Cultural War, Digital Memory in Brazil shows that the Bolsonaro government's digital memory of the Brazilian Dictatorship was never just about the past. Instead, it represents a political project aiming to reverberate in the Brazilian present and future. Innovating by crisscrossing digital memory concept with studies on right-wing populism and digital populism, Digital Memory in Brazil exposes the strategies and practices of one of the exponents of a global political trend.